Hi there, havn't done math in a while and I switched back to an advanced course so im a little behind. The question asks me to simplify I get this: = = It just doesn't feel right though, can you show me where I went wrong?
Follow Math Help Forum on Facebook and Google+
$(x^a)^b = x^{ab}$ NOT $x^{a+b}$ as you've done. $\dfrac{(3x^4 y^5 z^7)^5}{(-3x^3 y z^4)^7}=$ $\dfrac {3^5 x^{20} y^{25} z^{35}}{(-3)^7 x^{21} y^7 z^{28}}=$ $\dfrac {3^5 y^{18} z^7}{(-1)^7 (3)^7 x} =$ $-\dfrac{y^{18}z^7}{9x}$
thank you for clearing that up
View Tag Cloud